Methyl donors dietary supplementation to gestating sows diet improves the growth rate of offspring and is associating with changes in expression and DNA methylation of insulin‐like growth factor‐1 gene. Issue 5 (29th June 2018) - Jin, Chao; Zhuo, Yong; Wang, Jun; Zhao, Yang; Xuan, Yuedong; Mou, Daolin; Liu, Hong; Zhou, Pan; Fang, Zhengfeng; Che, Lianqiang; Xu, Shengyu; Feng, Bin; et al.
Abstract: The study aimed to investigate the effects of maternal dietary methyl donors on the performance of sows and their offspring, and the associated hepatic insulin‐like growth factor‐1 (IGF‐1) expression of the offspring. A total of 24 multiparous sows were randomly fed the control (CON) or the CON diet supplemented with methyl donors (MD) at 3 g/kg betaine, 15 mg/kg folic acid, 400 mg/kg choline and 150 μg/kg VB12, from mating until delivery. After farrowing, sows were fed a common lactation diet through a 28‐days lactation period and six litters per treatment were selected to be fed until at approximately 110 kg BW. Maternal MD supplementation resulted in greater birthweight ( p < 0.05) and increased the piglet weights ( p < 0.01) and litter weights ( p < 0.05) at the age of day 28, compared with that in CON group. The offspring pigs in the MD group had greater ADG ( p < 0.05) and tended to lower F:G ratio ( p = 0.07) compared with that of CON group from day 28 to 180 of age. The offspring pigs from MD group had greater serum IGF‐1 concentrations and expressions of hepatic IGF‐1 gene and muscular IGF‐1 receptor (IGF‐1r) protein at birth ( p < 0.05), and greater hepatic IGF‐1 protein ( p = 0.03) and muscular IGF‐1r gene expressions ( p < 0.05) at slaughter, than that from the CON group. Moreover, the methylation at the promoter of IGF‐1 gene in the liver of newborn piglets and finishing pigs was greater in the MD group than that of the CON group ( p < 0.05). In conclusion, maternal MD supplementation throughout gestation could enhance the birthweight and postnatal growth rate of offspring, associated with an increased expression of the IGF‐1 gene and IGF‐1r, as well as the altered DNA methylation of IGF‐1 gene promotor.